(NiSPOLNITELXSKAQ KULXTURA NARODNYH MUZYKALXNYH NARODNYH MUZYKALXNYH INSTRUMENTOW W rESPUBLIKE uZBEKISTAN(B.s (NuSTNAQ I PISXMENNAQ TRADICII(B.s - (NaNWAR lIWIEWs ((NtA[KENTs Nixol, 2010)
(NmONOGRAFIQ POSWQ]ENA (B70 -(NLETI@(B(1938)(NORKESTRA UZBEKSKIJ NARODNYH INTRUMENTOW I (B100-(NLETI@ (B(1910-2010) (NSO DNF ROVDENIQ a[OTA iWANOWI^A pETROSQNCA(B-(NSOZDATELQ I RUKOWODITELQ \TOGO ORKESTRA(B.s
Keywords: (NMONOGRAFIQs